2009
DOI: 10.2105/ajph.2008.133744
|View full text |Cite
|
Sign up to set email alerts
|

The Health of Older Mexican Americans in the Long Run

Abstract: Objectives-We compared risk for several medical illnesses between immigrant and US-born older Mexican Americans to determine the relationship between functional health and years of US residency among immigrants.Methods-Cross-sectional, multistage probability sample data for 3050 Mexican Americans aged 65 years or older from 5 US southwestern states were analyzed. Self-rated health, medical illnesses, and functional measures were examined in multivariate regression models that included nativity and years of US … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
50
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 50 publications
7
50
1
Order By: Relevance
“…Increased command of the English language is positively correlated with mortality among older Mexican Americans (12). Other researchers have found the opposite: improved functional health or maintained health is associated with more socioeconomic resources accrued with greater time in the United States (13,14). Longitudinal studies, thus, are needed to elucidate factors that contribute to the Hispanic paradox (11).…”
Section: Life Expectancy and The Hispanic Paradoxmentioning
confidence: 98%
“…Increased command of the English language is positively correlated with mortality among older Mexican Americans (12). Other researchers have found the opposite: improved functional health or maintained health is associated with more socioeconomic resources accrued with greater time in the United States (13,14). Longitudinal studies, thus, are needed to elucidate factors that contribute to the Hispanic paradox (11).…”
Section: Life Expectancy and The Hispanic Paradoxmentioning
confidence: 98%
“…González et al ., 2009), the relationship between acculturation and mental health appears to vary across one’s lifespan. Younger caregivers may be in a vulnerable stage establishing their own identity and family in addition to the tasks of caregiving; therefore, there may be other factors that more heavily influence depression.…”
Section: Discussionmentioning
confidence: 99%
“…A limited number of studies have examined the healthy immigrant effect in relation to older adult immigrants in the United States (e.g., Angel et al, 2010;Choi, 2012;González et al, 2009). These studies have reported observations of a reverse healthy immigrant effect that is similar to the findings of the Canadian research cited above (Gee et al, 2004;Kobayashi & Prus, 2012).…”
Section: Healthy Immigrant Effect In Relation To Older Adult Immigranmentioning
confidence: 99%
“…However, the samples of older adult immigrants used in these U.S. studies had immigrated before PRWORA was implemented. Choi (2012) used baseline data from 1994, whereas Angel et al (2010) and González et al (2009) used baseline data collected in 1993. Thus, their study participants were not affected by the PROWRA.…”
Section: Healthy Immigrant Effect In Relation To Older Adult Immigranmentioning
confidence: 99%
See 1 more Smart Citation